I have on me the evils of my people”. Interpellation and warning from the work of José Martí - Verdini-Aguilar, Marina (2016)
This is an historical analysis of the essay entitled Nuestra América, [Our America] written by the intellectual revolutionary José J. Martí. Knowing and analyzing the various historical contexts of our America have become key requirements in the pursuit of Marti’s libertarian praxis, given that, in present times, it is important to any approach that intends to contribute to the transformation of diverse situations of dependency and control that tend to mutate as the system changes that originated them. Within this framework, and as if recounting the past, we propose the development of a genuine epistemology whose contents question thought and revise customary ways of thinking. The study of several of Marti’s texts allows us to see the author's praxis as a complex that associates the history of his own revolutionary present with a clear, counter-hegemonic critique sui generis that we still consider to be relevant today.